(untitled) (Proceedings of International Conference on BioScience and Biotechnology, 2019)
The rich resource and raw material potential of Kazakhstan was the basis for the development of a powerful industry. However, it is industrial centers that are the areas of the highest pollution of the environment with heavy metals. A significant increase in the content of heavy metals in the environment is accompanied by their accumulation in plants, which has a negative impact on their growth, development and productivity. In this regard, the study of the reaction of plants to the action of heavy metals causes not only great scientific, but also practical interest. Different varieties of barley have been studied under conditions of natural soil contamination with heavy metals. The aim of the study is to identify resistant to cadmium and zinc barley varieties. The objects of the study are four varieties of barley from the collection of the East Kazakhstan Research Institute of Agriculture: Siberian Avant-Garde, Modern, Omsk, and Donetsk-8. The yield and survival of barley plants during the spring-summer vegetation were studied. Determination of physiological parameters was carried out according to the method of field experience. Productivity was determined by the direct method. Heavy metals (cadmium and zinc) were determined by atomic absorption with atomization in a flame and graphite furnace. The largest crop among the studied varieties has Modern variety of barley. The best survival is also demonstrated by Modern variety of barley. Donetsk-8 barley variety accumulates the least cadmium in the seeds. Siberian Avant-Garde barley variety accumulates the minimum amount of zinc in the seeds and at the same time is characterized by good survival during the spring-summer vegetation under conditions of polymetallic soil contamination.